Advancement in exosome-based cancer therapeutics: A new era in cancer treatment - Dutta, Abhishek; Paul, Swastika (Frontiers in Nanotechnology, 2022)
In the era of rapid therapeutic advancement in cancer management, there is a growing interest in the application of exosomes as a potential tool to target cancer cells. Exosomes are cell-derived nano-vesicles that modulate intercellular communications and transport. Due to their ideal native structure and characteristics, exosomes have emerged as a promising nanocarrier for clinical use. Nevertheless, their clinical application is associated with some inherent limitations which hinder their widespread use. In order to make exosomes more effective, they are engineered at the cellular level to develop designer exosomes. The focus of this review is to summarize the various exosome bio-engineering approaches aimed at the development of designer exosomes and their application in cancer treatment.